The effect of the probiotic "Rumit" on the growth activity of black-and-white calves - A. S. Litonina; Yu. M. Smirnova; A. V. Platonov (Аграрная наука Евро-Северо-Востока, 2022)
The object of the study is a probiotic Rumit produced by Biotrof Ltd., which can be added to the diet of milk-fed calves. It is developed on the basis of cellulolytic bacteria. In order to assess the effectiveness of the probiotic use there has been conducted a scientific and agricultural experiment on the basis of the agricultural production co-operative Kolkhoz Andoga of the Kaduysky district, Vologda region since March to June 2021. Studied were 20 calves of black-and- white bred aged 1.5-2 months divided according to the principle of paired peers into two groups: a control and an experimental. The experimental group was given the probiotic Rumit in the amount of 15 g/head/day during 90 days as a supplement to the basic diet. The data on live weight obtained in the course of the study indicate that the use of the probiotic in feeding calves has led to an increase in gross growth to 74.2 kg, that has provided a 3.8 % reduction in feed costs per unit of output.